There Is Plenty of Room in The Folded Globular Proteins: Tandem Modular Elastomeric Proteins Offer New Opportunities in Engineering Protein‐Based Biomaterials. Issue 7 (21st May 2021) - Li, Hongbin
Abstract : Shock absorber‐like elastomeric (SAE) proteins have become attractive building blocks to engineer protein hydrogels with tailored mechanical properties. These elastomeric proteins are tandem modular proteins consisting of individually folded globular domains and exhibit distinct mechanical properties. In response to stretching, folded globular domains can undergo force‐induced unfolding, leading to a significant change in protein stiffness and energy dissipation. These molecular behaviors of individual proteins can be harnessed and translated into macroscopic mechanical traits of protein hydrogels when such SAE proteins are used as building blocks to engineer protein hydrogels. These SAE proteins offer unique opportunities to rationally design protein‐based hydrogels by programming the mechanical properties of individual proteins at the molecular level, and thus help bridge the gap between biomechanics of macroscopic biomaterials and nanomechanics of single molecules. Abstract : Herein, an overview of the engineering of protein hydrogels based on shock absorber‐like elastomeric proteins is provided. The future outlook and challenges of this burgeoning field are also discussed.